STUDI BENTUK, FUNGSI, DAN MAKNA TINGKULUAK ADAT DI SUNGAYANG - Evan Ernanda, Dr. Syafwandi, M.Sn., Dra. Jupriani, M.Sn (Universitas Negeri Padang, 2018)
This research has a purpose to describe shape 1), function 2), and meaning 3) of motif tingkuluak adat in Sungayang This research is qualitative descriptive. Sources is primer data obtained from interviews with some informant. The source that is taken by the researcher such as: note (recordings, picture) which is gotten from informant by doing the interview, documentation, and study of literature. Shape, function, and neaning of tingkuluak adat bundo kanduang in Sungayang comes from nature and describe life of bundo kanduang and Minangkabau Society.Kata kunci: Bentuk, Fungsi, Makna